The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.12738/spc.2017.2.0024
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Death Anxiety and Meaning in Life Levels among Middle-Aged Adults

Abstract: Life and death constitute a whole, and these concepts become increasingly important in the evaluation of life among middleaged adults. Therefore, this study investigated the correlation between individual levels of death anxiety and meaning in life in terms of certain variables such as gender, age, educational status, marital status, perceived level of devoutness, and witness to death. The sample consisted of 185 individuals (82 males, 103 females; aged 25-55 years) living in Istanbul, Turkey. The data was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
(34 reference statements)
3
8
0
Order By: Relevance
“…As a result of the study, it was observed that the levels of anxiety sensitivity and resilience differed significantly in terms of marital status, but the level of death anxiety did not differ in terms of marital status. When the literature is examined, it is seen that marital status does not make a difference on death anxiety in the same way as the result of this research (Yüksel et al, 2017). In Yüksel et al's (2017) study , as in the current study, marital status does not make a difference on death anxiety in middle-aged adults.…”
Section: Discussionsupporting
confidence: 67%
“…As a result of the study, it was observed that the levels of anxiety sensitivity and resilience differed significantly in terms of marital status, but the level of death anxiety did not differ in terms of marital status. When the literature is examined, it is seen that marital status does not make a difference on death anxiety in the same way as the result of this research (Yüksel et al, 2017). In Yüksel et al's (2017) study , as in the current study, marital status does not make a difference on death anxiety in middle-aged adults.…”
Section: Discussionsupporting
confidence: 67%
“…Such individuals are prone to experiencing poor QoL (e.g., Cakmak & Gen, 2020; de Ornelas Maia et al, 2013) as they continually reflect on mortality-related issues and loss. Although the experience of diabetes and the knowledge of a protracted period of its management is potentially one existential crisis that is capable of arousing unpleasant feelings of hopelessness, helplessness, and/or emptiness, individuals who are able to find meaning in their lives, despite their health challenges, may effectively navigate this existential distress and cope adequately with their health conditions (Yuksel et al, 2017; Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Among diverse populations, a greater sense of meaning in life has been associated with decreased thoughts and worry about death (Yuksel et al, 2017; Zhang et al, 2019). The process of finding meaning in life in the face of a life-threatening illness may involve a deeper reflection on the individual’s health condition, the losses, the gains, and the desire to reconcile these experiences in a manner that positive lessons can be articulated, and the patients’ life objectives pursued.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Empirical research supports this idea, showing that those who are able to derive a sense of meaning in this way are most resilient against the mental health detriments associated with the awareness of inevitable death. 51,52 Similarly, Yüksel et al 53 report a negative correlation between meaning in life and death anxiety among middle-aged adults. In other words, death anxiety decreases as meaning in life increases (and vice versa).…”
Section: Creating Meaning In Lifementioning
confidence: 96%